FEATURES OF THE CLINICAL COURSE OF HYPOXIC-ISCHEMIC ENCEPHALOPATHY IN NEWBORNS - Tukhtaeva Mashkhura Mukhiddinovna (Web of Journals Publishing, 2024)
In the article are given date 60 newborns with gestation period from 28 to 41 weeks with hypoxic lesion of the CNS of the early period. The children were divided into 3 groups: 1 group of 20 newborns with GIE with gestation period 28-31 weeks, 2 groups of 20 newborns with GIE with gestation period of 32-37 weeks and 3 group of 20 newborns with GIE period and 38-4 gestation period.Teaching,that the degree of gestational maturity of the fruit determines the morphological features of cerebral damage, as well as the spectrum of somatic pathology of the neonatal period, in the analysis and presentation of the results obtained by the group as the main results.
Keywords: hypoxia, central nervous system, neonatal period, gestation period.